Astroglial NMDA receptors inhibit expression of Kir4.1 channels in glutamate-overexposed astrocytes in vitro and in the brain of rats with acute liver failure. (September 2015) - Obara-Michlewska, Marta; Ruszkiewicz, Joanna; Zielińska, Magdalena; Verkhratsky, Alexei; Albrecht, Jan
Highlights: Glutamate (Glu) and NMDA decrease Kir 4.1 expression in cultured astrocytes. Glu-induced loss of Kir 4.1 is reversed by NMDA receptor antagonists (NMDAra). Loss of brain Kir 4.1 mRNA in hepatic encephalopathy is attenuated by a NMDAra. Results implicate astrocytic NMDA receptors in Kir 4.1 loss in Glu-overexposed brain. Abstract: Astroglial inward rectifying Kir 4.1 potassium channels are fundamental for the maintenance of ion and water homeostasis in the central nervous system (CNS). Down-regulation of Kir 4.1 expression is observed in CNS disorders associated with excessive extracellular glutamate (Glu) accumulation, including hepatic encephalopathy related to acute liver failure (ALF). Here we demonstrate that prolonged (3 days) treatment of cultured rat cortical astrocytes with 2 mM Glu or 100 µM NMDA decreases the expression of Kir 4.1 mRNA and protein. Inhibition by Glu of Kir 4.1 mRNA expression was reversed by NMDA receptor antagonists MK-801 and AP-5 (each at 50 µM), and by a non-transportable inhibitor of Glu uptake TBOA (100 µM). MK-801 reversed the inhibitory effect of Glu on Kir 4.1 protein expression. In contrast, transcription of Kir 4.1 channels was not affected by: (i) a transportable Glu uptake inhibitor PDC (100 µM); (ii) by group I mGluR antagonist MTEP (100 µM); (iii) by antagonists of oxidative-nitrosative stress (ONS) in astrocytes, including the neuroprotective amino acid taurine (Tau; 10 mM), the NADPH oxidase inhibitor apocyanine (APO; 300 µM), the nitric oxide synthase inhibitor, L-NNA (100 µM), and a membrane permeable glutathione precursor, glutathione-diethyl ester (GEE; 3 mM). Down-regulation of Kir 4.1 transcription in rats with ALF was attenuated by intraperitoneal administration of a competitive NMDA receptor antagonist memantine, but not by histidine, which reverses ONS associated with ALF. Collectively, the results indicate that over-activation of astroglial NMDA receptors, aided by as yet undefined effects of Glu entry to astrocytes, is a primary cause of the reduction of Kir 4.1 expression in CNS disorders associated with increased exposure to Glu.